Population and distribution study of Austruca annulipes (ring-legged fiddler crab) in Ijo River Estuary mangrove, Kebumen, Central Java, Indonesia - Yap, Chee Kong; Setyawan, Ahmad Dwi; Rizky, Nur Fadilah; Yulia, Inggrid Trifena; Alfitra, Zhalzabilla Shafa; Armadhan, Winda Sagita; Widyaningtyas, Ratna; Rahmayani, Dita; Permatasari, Dinda Putri; Igustita, .; Kusuma, Dian; Prambudi, Satria Aji; et al. (Society for Indonesian Biodiversity, 2024)
Abstract. Fadilah RN, Yulia IT, Alfitra ZS, Armadhan WS, Widyaningtyas R, Rahmayani D, Permatasari DP, Igustita, Kusuma D, Prambudi SA, Berlin GE, Triyanto A, Yap CK, Setyawan AD. 2023. Population and distribution study of Austruca annulipes (ringlegged fiddler crab) in Ijo River Estuary Mangrove, Kebumen, Central Java, Indonesia. Pros Sem Nas Masy Biodiv Indon 9: 178-185. The mangrove ecosystem is an ecosystem that has a very important role, especially in the ecosystem services it provides. One of the typical faunas of the mangrove ecosystem is the Austruca annulipes (H. Milne-Edwards, 1837). This research aims to determine the population density and distribution pattern of A. annulipes in the Ijo River Estuary mangrove, Ayah, Kebumen, Indonesia. The research location was used for ecotourism, and its ecosystem needs to be evaluated to maintain its sustainability. One way to keep it is to identify the crustacean species because they have an essential role in the mangrove ecosystem and can be used as environmental bioindicator.. Data was collected using a purposive random sampling technique by 22 square plots making, measuring 10m x 10m. Furthermore, data were collected to document the morphology and activity of A. annulipes for identification, abiotic data; and the number of individuals to be analyzed using species density index and Morisita Index. The research shows that the population density of A. annulipes is 1.38 individuals/m2, and the Morisita Index value is 1.53 in clumped distribution category.